2019
DOI: 10.1002/jhbs.21992
|View full text |Cite
|
Sign up to set email alerts
|

Of Maslow, motives, and managers: The hierarchy of needs in American business, 1960–1985

Abstract: This paper examines the impact of psychologist Abraham Maslow's hierarchy of needs in American management. I trace how a roster of management experts translated the hierarchy of needs into management through case studies of job redesign programs at Texas Instruments and marketing firm Young & Rubicam's management training. The hierarchy of needs resonated with management, I argue, because it seemed to offer both a concrete guide for management, with practical implications for designing management training and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
0
25
0
1
Order By: Relevance
“…Earlier work on Maslow's needs theory corresponds well with our connection of the five dimensions of precarious employment to hierarchy of needs theory. Lussier (2019) documents suggestions by different authors (among them Maslow himself) to map the hierarchy of needs onto various workplace and employment characteristics. For example, physiological needs included financial compensation; safety needs included insurance, sick leave, and safety programmes; love and belonging needs included liking and respect gained from the job; esteem needs included job title, responsibility, recognition, and promotion; and self-actualization needs included a challenging job, creativity, and achievement in work (Berl et al, 1984;as cited in Lussier, 2019).…”
Section: Consequences Of Decent Work: Need Satisfaction and Capability Developmentmentioning
confidence: 99%
“…Earlier work on Maslow's needs theory corresponds well with our connection of the five dimensions of precarious employment to hierarchy of needs theory. Lussier (2019) documents suggestions by different authors (among them Maslow himself) to map the hierarchy of needs onto various workplace and employment characteristics. For example, physiological needs included financial compensation; safety needs included insurance, sick leave, and safety programmes; love and belonging needs included liking and respect gained from the job; esteem needs included job title, responsibility, recognition, and promotion; and self-actualization needs included a challenging job, creativity, and achievement in work (Berl et al, 1984;as cited in Lussier, 2019).…”
Section: Consequences Of Decent Work: Need Satisfaction and Capability Developmentmentioning
confidence: 99%
“…Psychological and safety needs in Maslow's theory are considered as biological needs for human survival, where individuals provide the basics to satisfy those needs and then move to satisfy the next level of needs (Maslow, 1962). Example of physiological needs include food, water, air, shelter, clothing, sex and individuals consume these items to satisfy their psychological needs (Lussier, 2019). But the religious beliefs have impacts on the purchase decision making process for this category needs, as various religions permit and prohibit the consumption of certain foods and diets to their followers.…”
Section: Information Searchmentioning
confidence: 99%
“…Maslow himself recognized extant resistance and suggested this resistance was the outcome of a scholarly pathology that created depressed, cynical, malicious, cruel, and vengeful members "of the intellectual community" who used their control of the channels of communication to the educated public and to youth" (A. H. Maslow, 1970, p. x) to suppress his theory. Some have suggested that user-friendly packaging (Lussier, 2019), face validity (Buttle, 1989), and basic explanatory value (Loh et al, 2000), at least when applied with broad brush strokes (Peterson & Park, 2010), keep the theory on the table. Others suggest it remains because it is "usable" (Loh et al, 2000).…”
Section: Deconstructing "Maslow's" Pyramidmentioning
confidence: 99%
“…Others suggest it remains because it is "usable" (Loh et al, 2000). As some have noted (Lussier, 2019), Maslow's theory provides actionable information to marketers and management seeking to understand and manipulate human behaviour and justify an exploitative system (Soper et al, 1995). Maslow's theory gives marketers a theoretical framework that allows them to conceptualize and effectively market products as capable of satisfying human needs (Peterson & Park, 2010, p. 320).…”
Section: Deconstructing "Maslow's" Pyramidmentioning
confidence: 99%
See 1 more Smart Citation